Hadamard Inequalities for Strongly α, m-Convex Functions via Caputo Fractional Derivatives. (6th January 2021) - Dong, Yanliang; Zeb, Muhammad; Farid, Ghulam; Bibi, Sidra
Abstract : In this paper, we present two versions of the Hadamard inequality for α, m convex functions via Caputo fractional derivatives. Several related results are analyzed for convex and m -convex functions along with their refinements and generalizations. The error bounds of the Hadamard inequalities are established by applying some known identities.